Preliminary Research: Identification Of Microorganism In The Waiting Room On Public Transportation Facilities, DKI Jakarta - Syarifah Miftahul El Jannah; Cahyawati Rahayu; Zuraida Zuraida; Rian Prasetio; Rizki Iman Sugiarto (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Public transportation is one of the places that have the potential to become a place of disease transmission, the discovery of bacteria in the facility is a public health problem is quite urgent. A preliminary test was conducted to find out the bacteria in waiting room at public transportation facilities in DKI Jakarta area. The research was conducted in cross sectional. Population are public facilities at the bus terminal of Kampung Rambutan, Pinang ranti, Manggarai, Grogol, Kalideres and Tanjung priuk. The sample is wipe the surface of iron fence, bench, handrail and counters as many as 24 samples. Conducted isolation on specific media and morphological, physiological and biochemical identification. We found 70 isolates with 5 species of bacteria, Staphylococcus aureus and Staphylococcus saphrophyticus 27.4%, Bacillus subtilis 25.7%, Staphylococcus epidermidis 17.14% and MRSA (Methicillin Resisten Staphylococcus Aureus) 2.8%. Locations with the most bacteria types are iron grip and chair. Tanjung priuk is place the most bacteria type and found MRSA. Method and frequency of cleaning of transportation means become one factor to eliminate number and type of microorganism. Until now there are no regulations that bind to the hygiene and sanitation of transportation in particular.